Pelatihan AI untuk Optimalisasi Kegiatan Yayasan IRMA Menuju Era Transformasi Digital - Taopik Hidayat; Syarah Seimahuira; Andi Saryoko; Retno Sari; Bagas Eka Saputra; Naufal Muzakki Ramadhan; Satrio Budi Santoso (P3M Politeknik Negeri Malang, 2025)
The rapid advancement of Artificial Intelligence (AI) technology is significantly influencing various sectors, including government and industry, by simplifying tasks traditionally performed by humans and creating new opportunities. The objective of this community service initiative was to enhance the technological skills of the caretakers at the Yayasan Santunan Yatim Piatu dan Sosial IRMA in South Jakarta, enabling them to utilize AI for daily activities and organizational needs. This program employed a three-step approach: preparation, implementation, and evaluation. In the preparation phase, challenges faced by the organization in adopting AI were identified, and necessary permissions were secured. The implementation phase involved interactive workshops focusing on computer usage and AI applications, fostering participant engagement through discussions and hands-on activities. Monitoring and evaluation were conducted using questionnaires to assess participant understanding and gather feedback on the training's effectiveness. Results indicated a marked improvement in participants' AI skills, enhancing their organizational capabilities and contributing positively to community development.